2021
DOI: 10.1021/acscatal.1c00795
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Photocatalytic Hydrogen Evolution Reaction Using Dual Plasmonic Antennas

Abstract: Plasmon-mediated photocatalytic water splitting has attracted extensive attention due to its bright future in using visible light, but the enhancement mechanism is still unclear, and the efficiency remains low. Herein, a dual-plasmonic-antenna strategy that allows efficient generation of energetic hot electrons and strong electromagnetic fields simultaneously has been developed to boost the photocatalytic hydrogen evolution reaction (HER). Au@CdS core–shell nanoparticles are assembled on Ag@SiO2 shell-isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 44 publications
0
47
1
Order By: Relevance
“…Yang et al synthesized hybrid dual plasmonic antenna consisting of partially CdS-coated Au satellites assembled on SiO 2 -coated Ag nanoparticles (Ag@SiO 2 /Au@CdS with pinholes). 132 Panels i and ii of Figure 3 c show the spatial arrangement of the metals. When tested for the HER, this structure yielded one of the highest performances for this type of PNP–SC hybrids (191 × 10 3 μmol g –1 h –1 , Figure 3 c).…”
Section: Plasmonic Metal–semiconductormentioning
confidence: 99%
“…Yang et al synthesized hybrid dual plasmonic antenna consisting of partially CdS-coated Au satellites assembled on SiO 2 -coated Ag nanoparticles (Ag@SiO 2 /Au@CdS with pinholes). 132 Panels i and ii of Figure 3 c show the spatial arrangement of the metals. When tested for the HER, this structure yielded one of the highest performances for this type of PNP–SC hybrids (191 × 10 3 μmol g –1 h –1 , Figure 3 c).…”
Section: Plasmonic Metal–semiconductormentioning
confidence: 99%
“…However, a significant obstacle to the industrialization of photocatalytic hydrogen production is low conversion efficiency. Many strategies have been therefore proposed to enhance the optical, electrical, and catalytic properties of photocatalysts to improve their efficiency, including heterojunction structural design [ 6 , 7 ], the introduction of plasmonic materials [ 8 , 9 , 10 ], defect engineering (e.g., oxygen or sulfur vacancy) [ 11 , 12 ], phase transition [ 13 , 14 ], and single-atom catalysis [ 15 , 16 , 17 ]. It is worth noting that catalysis is a surface redox reaction on the photocatalyst, where the water molecules split into hydrogen and oxygen [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the better activity of the Au-Cu 2−x Te heterostructure toward HER was mainly due to the more electron-abundant Au, which is attributed to the additional reductive sites for hydrogen ion reduction, thereby facilitating the spontaneous charge transfer between metal and semiconductors and resulting in their intrinsic catalytic activity. 4 The corresponding Tafel plots of the pure Cu 2−x Te and Au-Cu 2−x Te heterostructures are presented in Figure 3b, to reveal the hydrogen evolution kinetics of the catalysts loaded working electrode. From the data, it was observed that the Tafel slope for heterostructure materials was about 154 mV/dec, smaller than that for pure Cu 2−x Te (183 mV/dec).…”
mentioning
confidence: 99%
“…Plasmonic heteronanostructures are widely established as the leading optical material for photochemical and photoelectrochemical (PEC) reactions. The exciton–plasmon coupling remained a key feature for boosting the charge carrier transfer and enhancing the catalytic activity of these materials. To overcome the global energy crisis and environmental issues, production of a clean energy source like hydrogen using these heterostructured catalysts as one of the renewable methods has also been widely explored. Among these, dual plasmonic nanostructures remained in a special category for their higher absorption ability and efficient photogenerated charge carrier transportation. ,, Au-Cu 2– x S and Au-Cu 2– x Se are the most common Au coupled copper based chalcogenide heterostructures, and these were also explored for catalysis in HER, OER, and CO 2 RR. ,, The importance of such materials with Cu­(I) is due to their stoichiometry, where some percentage of Cu­(I) either remains vacant or is transformed to Cu­(II), which induces localized surface plasmon resonance (LSPR) in these materials. Hence, adding plasmonic Au to these copper compounds invariably boosts the dual plasmonic character, ideal for electrocatalytic (EC) and PEC reactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation